Status Ontologis Toleransi dalam Ide Politik Otentik di Indonesia - Putra, Surya Desismansyah Eka (Universitas Nusantara PGRI Kediri, 2022)
The essence of tolerance in this era often collided with the conflict between the idea of ​​inclusivity and the idea of ​​exclusivity towards the democratic values ​​of citizenship. Surveys from various social and educational institutions that wish to develop the primacy of tolerance, namely humanity, are trapped in limited narratives about behaviour and perspectives through schematic questions. Tolerance is a phenomenon with articulation manifested in political policies and the facilities provided. Therefore, the nature of tolerance needs to be sued again. This article is analyzed using literature and case studies in the mass media. The results of the analysis of this article are (a) the ontological status of tolerance in Indonesia is humanity, justice and freedom or independence as a nation, (b) tolerance is a concrete attitude and behaviour whobehaviourrement is through pro-equality citizens policies and is realized in available public facilities, and (c) efforts to achieve tolerance can only be realized by starting authentic political practices, namely politics that stops the arbitrary desire of the authorities to return to the awareness that politics is a way of liberation as well as a way to disagree.